Immunobiotic potential of fermented snail meat hydrolysate in local chicken with low protein content - Suryadi, Ujang; Hertamawati, Rosa Tri; Imam, Shokhirul (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: Protein is needed for chicken growth, but high protein consumption causes a low protein efficiency ratio and causes feed prices to be expensive. Therefore, the immunological potential of fermented snail meat hydrolysate in local chickens was studied for feed supplements in low-protein rations to reduce costs. Materials and Methods: The research used snail meat hydrolysate resulting from submerged fermentation with starter culture from rice washing water. Using hydrolysates as a fishmeal substitute to reduce the protein content of male local chicken diets. Hydrolysate is mixed into the formulated ration: P0 = 12% fish meal in feed without hydrolysate added, P1 = 8% fish meal in feed plus 5 ml hydrolysate/kg feed; P2 = 4% fish meal in feed plus 10 ml hydrolysate/kg feed; and P3 = Feed without fish meal plus 15 ml hydrolysate/kg feed. The study used completely randomized study parameters, namely the production performance of 200 chickens and the immune system (including lymphoid organs and hematological status) of 60 chickens. Results: Snail meat hydrolysate (10 ml/kg) can replace the reduction in the use of fish meal from 12% to 4% in ration formulation without reducing production performance and has no negative effect on the immune system. Conclusion: Snail meat hydrolysate has the potential to be used as an immune antibiotic to replace the use of fishmeal in the development of low-protein dietary formulations without affecting production performance or negatively affecting the chicken's immune system. Adv. Vet. Anim. Res., 11(1): 71-77, March 2024 http://doi.org/10.5455/javar.2024.k749